(untitled) (Brazilian Geographical Journal, 2017)
We have seen in Brazil the last decade as a period of expansion of income and consumption, especially by low purchase power classes. This expansion translates in decrease of socio-economic inequalities. However, the existing cities are highly marked by socio-spatial inequalities and nowadays present the tendency of increase of social segmentation. This reality questions the right to city as a possibility of revalorising the urban life and its sharing. Space is also questioned as mediation of collective life and, as a result, socio-spatial fragmentation erupts as a tendency of contemporary urbanisation. The analysis consists in questioning the right to consumption as potential substitute to the right to city and thinking about the persistence of this right in contexts marked by socio-spatial fragmentation. The presented ideas are based on concluded researches as well as on hypotheses taken from researches currently made in São Paulo state’s intermediate cities. The methodology is based on contrapositions of author’s ideas and interviews with citizens.